2020
DOI: 10.1039/d0cy01526a
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature and atmospheric pressure aqueous partial oxidation of ethane to oxygenates over AuPd catalysts

Abstract: New modes of chemical manufacturing based on small-scale, distributed facilities have been proposed to supplement many existing production operations in the chemical industry, including the synthesis of value-added products from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is well-known that C 2 H 5 OOH is produced via the reaction of H 2 O 2 and ethane. 7,11 Therefore, the observation of C 2 H 5 OOH in this system suggests that H 2 O 2 is formed under the reaction, and the supported Pt catalyst uses it as an oxidant to catalyze the ethane oxidation. To verify this hypothesis, Ce(SO 4 ) 2 titration was performed on the postreaction solutions (Table 2).…”
Section: Effect Of Msis On Catalyticmentioning
confidence: 82%
See 2 more Smart Citations
“…It is well-known that C 2 H 5 OOH is produced via the reaction of H 2 O 2 and ethane. 7,11 Therefore, the observation of C 2 H 5 OOH in this system suggests that H 2 O 2 is formed under the reaction, and the supported Pt catalyst uses it as an oxidant to catalyze the ethane oxidation. To verify this hypothesis, Ce(SO 4 ) 2 titration was performed on the postreaction solutions (Table 2).…”
Section: Effect Of Msis On Catalyticmentioning
confidence: 82%
“…The former system, especially with O 2 as an oxidant, is an attractive reaction system because the target product can be easily separated from the catalytic system. However, the reaction requires high temperatures, and the reaction rate and ethanol selectivity are extremely low. Oxidation of ethane to ethanol using H 2 O 2 as an oxidant has also been reported. The H 2 O 2 generates the reactive oxygen species and boosts the partial oxidation of ethane. However, the ethanol selectivity is 53% at the highest. Since H 2 O 2 is expensive, a reaction system using O 2 as the oxidant is more desirable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold catalysts have been widely used in many reactions as shown by several reviews [46][47][48][49]. However, the only references found in the literature for the use of gold in ethane oxidation are from the work of Wang et al, dealing with non-supported Au-Pd nanoparticles in water, but the main product obtained was ethyl hydroperoxide [50] and our own work dealing with homogeneous N-heterocyclic carbene and oxo-carbene Au(I) compounds [51]. Therefore, to the best of our knowledge, the present work reports the first use of commercial gold complexes supported on carbon nanomaterials in the oxidation of ethane to produce acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to develop a direct conversion path of ethane under lower temperature conditions. There have been not so many reports on the direct conversion of ethane under mild conditions [2][3][4][21][22][23][24] . Hutchings et al found that ethane could be directly converted to ethanol and ethyl hydroperoxide, which would be further oxidized to acetaldehyde and acetic acid at 323 K on Fe-ZSM-5 catalyst using H 2 O 2 21 .…”
mentioning
confidence: 99%